Pengaruh manajemen kinerja terhadap peningkatan kinerja pengelola di UPTD BBIAT Kota Cimahi - Mansur, Ahmad; Susilawati, Susilawati; Suryaman, Warman (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Performance is an achievement of the success or failure of organizational goals that have been set Information about organizational performance is a very important thing that is used to evaluate whether the performance process carried out by the organization so far is in line with the expected goals or not. In government agencies, the need is not much different. This study was conducted with the aim of examining the effect of performance management on the performance of managers in the Regional Technical Implementation Unit (UPTD) in Cimahi City. The research method used by researchers is descriptive and verification research. The number of samples studied was 30 people using saturated samples. Data analysis using simple linear regression analysis. From the results of data analysis conducted, it is proven that performance management can positively affect the performance of managers at the UPTD Freshwater Fish Seed Center (BBIAT) Cimahi City. The findings of this study are that there is an effect of performance management on the performance of managers at UPTD BBIAT Cimahi city, while the magnitude of the influence of the performance management variable is 0.776 or 77.6%, and the remaining 22.4% is influenced by other factors.